Third harmonic injection pulse-width modulation technique for a five-phase voltage source inverter - Yasir M.Y. Ameen; Bashar A. Fadheel; Ali J Mahdi (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Nowadays application of advanced power electronic technology enables producing an AC supply with a phase number higher than three-phase. Five-phase voltage source inverters (5ph-VSI) have been used in advanced power electronic drives to improve the reliability of the drive system and to boost the power capability of the converter as well as to their other inherent merits. This paper shows the mathematical analysis and simulation of the third harmonic injection pulse width modulation (THI-PWM) 5ph-VSI connected with inductive load in three scenarios i.e. star, Pentagon and pentacle. The presented THI-PWM technique for 5ph-VSI aims to increase the inverter fundamental voltage and hence to maximize the utilization of the DC bus without causing over-modulation. The simulation results are compared with typical sinusoidal pulse width modulation (SPWM) and the 10-step mode operation. The proposed scheme may be considered as a compromise case between the two reference cases;  as low harmonic components compared with 10-step mode operation and a high utilization factor compared with SPWM.